Perlindungan Hukum terhadap Merek Terkenal dari Praktik Cybersquatting di Indonesia - Tjahyono, Dwi; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of information technology has contributed to the emergence of cybersquatting, namely the registration of domain names that imitate well-known trademarks in bad faith for economic gain. This study aims to analyze the legal framework, forms of legal protection, dispute resolution mechanisms, and the effectiveness of Indonesian law in protecting well-known trademarks against cybersquatting. The research employs a normative juridical method using statutory, conceptual, and comparative approaches, examining Law Number 20 of 2016 on Trademarks and Geographical Indications, the Electronic Information and Transactions Law and its amendments, PANDI’s Domain Name Dispute Resolution Policy, and the Uniform Domain Name Dispute Resolution Policy (UDRP). The findings reveal that legal protection remains fragmented, relying on trademark law, cyber law, and PANDI’s administrative policy. Stronger regulatory harmonization, clearer standards for proving bad faith, and specific legislation are necessary to ensure legal certainty in the digital economy.